A look into atomic carbon and oxygen adsorption on 1T′-MoS2 monolayer: density functional theory calculations. (13th December 2017) - Barayang Putungan, Darwin; Lin, Shi-Hsin
Abstract: In this work, we looked into the adsorption and diffusion properties of atomic carbon and oxygen on the basal plane of 1T′-MoS2 monolayer via density functional theory calculations. Due to the 2 × 1 reconstruction in single-layer 1T′-MoS2, two distinct adsorption sites for atomic carbon and oxygen were identified: S T (longer Mo-S bond length similar to the effect of a tensile strain) and S C (shorter Mo-S bond similar to the effect of a compressive strain). In all cases, carbon and oxygen adsorb stronger on the S T site, with oxygen binding higher by up to 1 eV on both sites. Moreover, it is found that carbon and oxygen hopping from an S T site to a nearby S C site is described by very high diffusion barriers, which implies poor atomic mobility on the surface but nevertheless could be useful is certain film deposition processes and surface functionalization. It is further found that applying biaxial tensile strain on 1T′-MoS2 affects carbon and oxygen adsorption differently: carbon binding on both S T and S C sites shows a dramatic change in the adsorption energy resulting to an irregular adsorption energy trend with increasing biaxial strain, while oxygen binding appears to be negligibly affected, with very minimal changes in the adsorption energy. These results are of importance in the assessment of certain dissociation reactions on the surface, such as that of CO and O2, including how biaxial strain affects the adsorption of each by-product atoms.